2021
DOI: 10.1155/2021/8497305
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma with Mixed Subtypes in the Early and Advanced Gastric Cancer

Abstract: Objective. Adenocarcinoma with mixed subtypes (AM) is a histological classification based on the WHO classification. We aimed to compare the prognosis among AM, classic adenocarcinoma (CA), mucinous adenocarcinoma (MAC), and signet-ring cell carcinoma (SRCC) in early and advanced gastric cancer (EGC and AGC), respectively. Methods. The Surveillance, Epidemiology, and End Results (SEER) database was queried from 2001 to 2016. Univariate and multivariate Cox analyses were performed to compare prognosis between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…In histological type, we found that the prognosis of undifferentiated carcinoma was the worst in both OS and CSS, while the prognosis of signet ring cell carcinoma (SRCC) and adenocarcinoma did not differ significantly. This is consistent with the study of Zhao et al, who found little difference in the prognosis of the three types of adenocarcinomas (mixed, classic, and mucinous) and SRCC in advanced gastric cancer (40).…”
Section: Discussionsupporting
confidence: 93%
“…In histological type, we found that the prognosis of undifferentiated carcinoma was the worst in both OS and CSS, while the prognosis of signet ring cell carcinoma (SRCC) and adenocarcinoma did not differ significantly. This is consistent with the study of Zhao et al, who found little difference in the prognosis of the three types of adenocarcinomas (mixed, classic, and mucinous) and SRCC in advanced gastric cancer (40).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, LNM rate of mixed type EGC was higher than rate of pure histology type EGC (16.6% vs. 6.1%, p < 0.01), which supports some of the previous reports ( 24 26 ). However, we revealed a pattern that clinicopathological features including LNM rate differ according to PUC level.…”
Section: Discussionsupporting
confidence: 91%
“…Several parameters such as LVI, tumor size, invasion depth, presence of ulcer had been confirmed to be related to LNM in EGC. Several previous studies showed that EGC with mixed histological type was more aggressive ( 24 26 ), but none of the studies focused on the PUC levels, which might be different on clinicopathological features and related to LNM in EGC. Since proportion of each histologic type varies widely in different EGC lesions, we investigated clinicopathological features of EGC according to different PUC levels.…”
Section: Discussionmentioning
confidence: 98%
“…Heger U (2014) [8]; Hsu JT (2016) [60]; Imamura T (2016) [34]; Jiang CG (2011) [53]; Kao YC (2019) [68]; Khan N (2020) [82]; Lemoine N (2016) [77]; Liu X (2015) [59]; Lu M (2016) [62]; Luu C (2017) [88]; Men HT (2016) [49]; Piessen G (2012) [79]; Postlewait LM (2015) [85]; Riihimäki M (2016) [78]; Schmidt T (2014) [80]; Shim JH (2014) [58]; Shridhar R (2013) [83]; Taghavi S (2012) [84]; Tang CT (2020) [90]; Voron T (2016) [81]; Wang Z (2015) [32]; Zhao X (2021) [92]; Zu H (2014) [46].…”
Section: Lymphovascular Invasionmentioning
confidence: 99%